Motivation to Learn to Read Al-Qur'an Students - Suriyani, Ellya; Desi, Desi (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: Motivation to learn to read the Qur'an is a driving force that arises both from outside and from within a person or student who encourages them to carry out noble worship activities whose rewards are multiplied by Allah if they read them seriously and play an important role in giving enthusiasm, enthusiasm and pleasure in learning to read Al-Qur'an. The purpose of this study was to determine the motivation to learn to read the Qur'an of students at Madrasah Nurul Jihad, indicators of learning motivation. Methodology: This type of research is a qualitative descriptive research. The population in this study were 13 grade IV students and 28 grade V students at Madrasah Nurul Jihad. Data in this study were collected using questionnaires, interviews and documentation. Furthermore, the collected data was analyzed using the percentage formula. Main Findings: The research shows that: students of grades IV and V at Madrasah Nurul Jihad are very good at learning to read Al-Qur'an. All learning activities to read the Qur'an are carried out, but not optimal or perfect. The indicator of learning motivation is taken from the operational concept. Novelty/Originality of this study: This research presents findings that illustrate how the madrasah environment, family support, and students' internal factors influence their motivation to master the skill of reading the Al-Qur'an. By understanding these motivations, this research provides valuable insights into the development of more effective and in-depth learning approaches in the madrasa context, which can increase interest and quality of Al-Qur'an learning for students.